Etyczne aspekty globalizacji gospodarki - Sobuś, Paweł Bogumił (Annales. Etyka w Życiu Gospodarczym, 2011)
The globalization constitutes the multilevel phenomenon. It also concerns the economic sphere. It is connected with the rapidtechnological development. In order to achieve this increasingly more recent economic successes do not forget about the one,who is to be source and the purpose of any activity – of a man.